1995
DOI: 10.1111/j.2044-8260.1995.tb01452.x
|View full text |Cite
|
Sign up to set email alerts
|

Death and people with learning disabilities: Interventions to support clients and carers

Abstract: The needs of people with learning disabilities who are bereaved have been acknowledged in the last decade. There is more understanding of ways to meet these needs. Carers need training and support when working with people who are dying or bereaved. This paper reviews the relevant literature, offers guidelines for practice and highlights areas for further development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 9 publications
0
24
0
1
Order By: Relevance
“…Parkes, 1998), relating to bereavement in adult life, has indicated a manifest need for further research on the factors that affect the duration and outcome of bereavement, and on methods by which detrimental effects can be foreseen, recognised and alleviated. A review by Cathcart (1995) showed that practical interventions and resources now exist in some areas, and others are currently being developed, in order to mitigate the distressing effects of bereavement on people with learning disabilities.…”
Section: Bereavementmentioning
confidence: 99%
“…Parkes, 1998), relating to bereavement in adult life, has indicated a manifest need for further research on the factors that affect the duration and outcome of bereavement, and on methods by which detrimental effects can be foreseen, recognised and alleviated. A review by Cathcart (1995) showed that practical interventions and resources now exist in some areas, and others are currently being developed, in order to mitigate the distressing effects of bereavement on people with learning disabilities.…”
Section: Bereavementmentioning
confidence: 99%
“…However, other people, because of their difficulties associated with their level of intellectual disabilities (for example, comprehension, communication skills, lack of supports), may display grief in alternative mannerisms, many of which have been described as 'challenging' (MacHale and Carey, 2002;Read and Papakosta-Harvey, 2004;Dodd et al, 2005). Cathcart (1995) has further argued that these 'challenging behaviours' and also possible 'psychiatric disturbances' may be the only mechanisms available to those with significant cognitive and communication impairments. Hollins and Esterhuyzen (1997) found that of 50 people with intellectual disabilities who had experienced bereavement and exhibited an array of challenging behaviours, nearly three-quarters of their carers did not attribute these behavioural changes as expressions of grief.…”
mentioning
confidence: 97%
“…It has been broadly reported that, for many people with intellectual disabilities who experience a bereavement, they can experience the same range and degrees of emotions (for example, sadness, anger, anxiety, loneliness), physical sensations (for example, hollowness in stomach, lack of energy) and behaviours (for example, sleep and appetite disturbances, withdrawal) as displayed within the non-disabled population (Oswin, 1991;Cathcart, 1991Cathcart, , 1995Read, 2005). However, other people, because of their difficulties associated with their level of intellectual disabilities (for example, comprehension, communication skills, lack of supports), may display grief in alternative mannerisms, many of which have been described as 'challenging' (MacHale and Carey, 2002;Read and Papakosta-Harvey, 2004;Dodd et al, 2005).…”
mentioning
confidence: 98%
“…Finally, it has now been recognized that grief is experienced by people with mental retardation (e.g. Cathcart, 1995). Therefore, mood assessment could help monitor reactions to life-events, including bereavement, staff changes or changes in residence for people who are unable to talk about their thoughts and feelings.…”
Section: Evaluating Interventions Designed To Reduce "Challenging Behmentioning
confidence: 99%
“…Benson, Rice & Miranti, 1986;Benson, 1994) and bereavement (e.g. Cathcart, 1995). Less interest has been paid to mood and emotions amongst people with severe and profound mental retardation (Favell, Realon & Sutton, 1996).…”
Section: Introductionmentioning
confidence: 99%